Tunable two-dimensional polarization grating using a self-organized micropixelated liquid crystal structure. Issue 72 (12th December 2018) - Amano, Reo; Salamon, Péter; Yokokawa, Shunsuke; Kobayashi, Fumiaki; Sasaki, Yuji; Fujii, Shuji; Buka, Ágnes; Araoka, Fumito; Orihara, Hiroshi
Abstract : A micro-pixelated pattern of a nematic liquid crystal formed by self-organization of topological defects is shown to work as a tunable two-dimensional optical grating. Abstract : Utilization of the self-organizing nature of soft materials is promising for fabricating micro- and nano-structures, which can be applied for optics. Because of the high birefringence, liquid crystals are especially suitable for optoelectronic applications such as beam steering and polarization conversion. On the other hand, most self-organized patterns in liquid crystals are one-dimensional and there are only a few examples of two dimensional systems. Here we study the light diffraction from a micro-pixelated pattern of a nematic liquid crystal which is formed by self-organization of topological defects. We demonstrate that the system works as a tunable two dimensional optical grating, which splits the incident laser beam and changes the polarization property. The intensity can be controlled by electrical voltages, which cause extinction of the zeroth-order beam. The polarization properties depend on the location of spots. The numerical calculation and the theoretical analysis not only support the experimental results but also unveil the uniqueness of the pixelated structure.